Gastona Bachelarda psychoanaliza umysłu naukowego - Ples-Bęben, Marta (Folia Philosophica, 2018)
The paper concerns the psychoanalysis of objective cognition — a philosophical project by Gaston Bachelard, developed and implemented in epistemology and philosophy of science since 1938. The paper consists of two parts. Firstly, relation between Bachelard’s philosophy and psychoanalysis is addressed with the special attention given to sources of Bachelard’s inspiration — S. Freud, C.G. Jung, M. Bonaparte and R. Allendy. Secondly, Bachelard’s concept of psychoanalysis of objective cognition is discussed. In the course of its development, Bachelard transformed the assumptions and ideas of Freud and Jung and used them in theory of knowledge and philosophy of science. This original project was straightforwardly practical — it was aimed at providing an analysis of the scientific mind, revealing any epistemological obstacles it contains (such as false beliefs and habits of thinking) and its overcoming so that valuable cognition might be obtained.